Kultur Nahdlatul Ulama Dalam Penerapan Akad Syariah - Nadila Meiri Syahdana; Norsain Norsain (JPS (Jurnal Perbankan Syariah), 2021)
The first step in building a good ummah or mabadi' khaira ummah, Nahdlatul Ulama (NU) instilled the five characteristics of the Prophet to his people so that they have a strong mentality as a capital for social-economic improvement in society. The purpose of this study was to analyze the culture of NU in the application of sharia contracts at KSPS BMT UGT Sidogiri, Lenteng Branch. This study uses a qualitative method with a case study approach. The data obtained by researchers are primary data from interviews, observation and documentation. The results of this study indicate that some of the characteristics of mabadi' khaira ummah, namely shiddiq and amanah, are applied in KSPS BMT UGT Sidogiri, Lenteng Branch. Attitudes tawassuth-i'tidal, tasamuh, tawazzun and amar ma'ruf nahi munkar are applied to employee behavior.